Sex differences in connectivity in the default mode network in healthy aging adults. (31st December 2021) - Ficek, Bronte; Horien, Corey; Lacadie, Cheryl; Shen, Xilin; Scheinost, Dustin; Constable, Todd; Fredericks, Carolyn A
Abstract: Background: Two‐thirds of individuals diagnosed with Alzheimer's disease (AD) are women, but the reasons for women's elevated risk are unknown, and sex differences in brain aging trajectories are poorly understood. Both symptomatic AD and aging are associated with decreased connectivity within the default mode network (DMN), which supports short‐term memory processing, while individuals with preclinical AD show increased connectivity in some DMN regions. We sought to identify sex‐based differences in DMN connectivity over the lifespan in a large cross‐sectional study of healthy adults. Method: We examined functional MRI data from a cross‐sectional cohort of n=595 cognitively normal individuals (aged 36‐100 years; 249 females) drawn from the Human Connectome Project‐Aging (HCP‐A) dataset (Harms et al., 2018; Bookheimer et al., 2019). Preprocessing followed our previously described pipeline, with stringent motion thresholds applied. The four resting‐state scans for each individual were averaged and masked to a standard DMN parcellation (Yeo et al., 2011). We calculated within‐network connectivity of each DMN voxel using the intrinsic connectivity distribution (ICD) (Scheinost et al., 2012), a robust voxel‐based metric of functional connectivity, and used a general linear model to assess the main effect of sex on within‐network ICD with increasing age. Result: Females showed relative hyperconnectivity in posterior DMN with age compared to males, but lower connectivity in anterior nodes (Fig 1). Specifically, z‐scores for female minus male contrasts for posterior clusters were 3.9 (posterior cingulate), 4.5 (R angular gyrus), and 4.7 (L), and for anterior clusters were ‐4.1 (R frontal pole) and ‐4.3 (L). Conclusion: In a large sample of healthy aging adults, women showed increased connectivity in posterior, and decreased connectivity in anterior, nodes of the DMN compared with their aging male counterparts. Interestingly, individuals with preclinical AD show a similar pattern of posterior hyperconnectivity, often interpreted as the compensatory response of a network under stress. These findings provide early clues to a potential role for network‐level sex differences in explaining women's increased vulnerability to AD as they age.